2016
DOI: 10.1016/j.jenvp.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Stairway to heaven? (Ir)religious identity moderates the effects of immersion in religious spaces on self-esteem and self-perceived physical health

Abstract: The present research explored how immersion in religious spaces influenced self-perceived psychological and physical health among Christians and Atheists. Study 1 (N=97) provided preliminary evidence in that self-identified Christians reported higher self-esteem when they focused on their external environment outside a cathedral (versus a castle or shopping district), whereas Atheists reported higher self-esteem when they focused away from this religious environment. Study 2 (N=124) followed up on these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
5
26
0
Order By: Relevance
“…Additionally, the researchers found that residents who were strongly identified with their neighbourhood had higher self-esteem,a finding which accords with previous studies that have examined the relationship between place-related identities and self-esteem (Knez, 2005;Fleury-Bahi & Marcouyeux, 2010;Twigger Ross & Uzzell, 1996). Along similar lines, other research informed by the social identity approach has shown that psychological wellbeing associated with restorative (Morton, van der Bles & Haslam, 2017), spiritual (Ysseldyk, Haslam, & Morton, 2016) and festive (Schmitt, Davies, Hung, & Wright, 2010) environments are shaped by social group identification.…”
Section: Social Identification Perceived Neighbourhood Quality and Msupporting
confidence: 81%
“…Additionally, the researchers found that residents who were strongly identified with their neighbourhood had higher self-esteem,a finding which accords with previous studies that have examined the relationship between place-related identities and self-esteem (Knez, 2005;Fleury-Bahi & Marcouyeux, 2010;Twigger Ross & Uzzell, 1996). Along similar lines, other research informed by the social identity approach has shown that psychological wellbeing associated with restorative (Morton, van der Bles & Haslam, 2017), spiritual (Ysseldyk, Haslam, & Morton, 2016) and festive (Schmitt, Davies, Hung, & Wright, 2010) environments are shaped by social group identification.…”
Section: Social Identification Perceived Neighbourhood Quality and Msupporting
confidence: 81%
“…The present studies join a number of recent works that have extended these insights to the experience of physical environments, for example by showing that social identities determine the psychological consequences of being in specific spaces (e.g., Cheryan et al, 2009;Knight & Haslam, 2010a & b;Schmitt et al, 2010;Ysseldyk, Haslam & Morton, 2016) and help to explain when and why objectively M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, there was some evidence in our own data that individual differences in nature-based self-definition (i.e., connectedness to nature) guided cognitive responses to natural and urban images in a similar way to our identity manipulation (see Footnote 7). Other studies that have explored identity-based responses to other environmental features have made use of enduring categorical identities, for example, those based on religion (Shankar et al, 2013;Schmitt et al, 2010;Ysseldyk et al, 2016) and gender (Cheryan et al, 2009). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In regards to the elicitation of awe, one study found that reported physical health was improved when Christians were immersed in a cathedral (versus a mosque or museum). By contrast, atheists reported the greatest health while disengaging from this religious setting (Ysseldyk, Haslam, & Morton, 2016). What may be labelled as "spiritual" experiences for the nonreligious tend to be elicited via different sources than for the religious (e.g., nature, science, secular versions of yoga or meditation; see Figure 1), although these may ultimately function via shared common pathway with R/S versions of experiences (Preston & Shin, 2017).…”
Section: Secular Needs Experiences and Practicesmentioning
confidence: 99%